Pemetaan Bibliometrik Berbasis Co-Word Tentang Gerakan Literasi Sekolah (GLS) Di Indonesia - Azizah, Nur; Winoto, Yunus (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2023)
Abstract : In Indonesia, information literacy shows a worrying sign. The Program for International Student Assessment (PISA) in its research released by the Organization for Economic Co-operation and Development (OECD) in 2010 revealed that the reading position of students in Indonesia is in the 57th position out of 65 countries. Therefore, through the Minister of Education and Culture of the Republic of Indonesia Number 23 of 2015 concerning the Growth of Character, the School Literacy Movement (GLS) was implemented in Indonesia. This GLS is done by habituating students to read books other than textbooks for 15 minutes before class starts. This is intended to increase student motivation so that later they achieve ideal information literacy. The intensive implementation of the GLS encourages researchers to find out how far has the development of scientific publications in the field of GLS been. The research method was carried out by obtaining data through Publish or Perish and bibliometric mapping was carried out by co-word analysis using the vos viewer. The results of this study are network visualization, overlay visualization, and density visualization from GLS scientific publications in Indonesia for a period of 6 years (2015-2021).